Systematic study on QAMS method for simultaneous determination of triterpenoid saponins in Ilex pubescens by HPLC and UPLC. Issue 16 (21st August 2015) - Kuang, Guojun; Zhou, Jie; Yao, Meicun; Tan, Qinglong; Qi, Longkai; Liang, Jianhui; Li, Yu; Zhao, Zhongxiang; Zhang, Lei
<x xml:space="preserve">Abstract</x> A linear regression method (LRG) had higher accuracy than an average method (AVG) and the concentration of the quantitative component was the major influencing parameter of the accuracy of the QAMS method.